The Effect of Work Environment Quality and Work Motivation on Performance Through Employee Job Satisfaction in Bondowoso District Office - Wiwik Supriyatin; Handayani, Yuniorita Indah Handayani; Muhaimin Dimyati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The problem in this research is that several employee performance assessments tend to decline, including service orientation, integrity, discipline and cooperation. The decline in performance is thought to be caused by several things, including a lack of quality of the work environment and job satisfaction that have not been fully met. The aim of this research is to test and analyze the influence of the environment and work motivation on employee performance through job satisfaction as an intervening variable at the Bondowoso District Office, Bondowoso Regency. This research was included in confirmatory research with a population and sample of 115 respondents, a saturated sampling technique was used because the entire population was used as the sample. The data analysis technique used is Structural Equation Modeling (SEM) processed with Smart PLS 4.0. Based on the results of data analysis, it shows that the quality of the work environment has a significant effect on job satisfaction. Work motivation has a significant effect on job satisfaction at the Bondowoso District Office, Bondowoso Regency. The quality of the work environment, work motivation and job satisfaction have a significant effect on employee performance at the Bondowoso District Office, Bondowoso Regency. The quality of the work environment has a significant effect on employee performance through job satisfaction at the Bondowoso District Office, Bondowoso Regency. Work motivation has a significant effect on employee performance through job satisfaction at the Bondowoso District Office, Bondowoso Regency